Pain Management After Cesarean Delivery Among Women with Opioid Use Disorder: Results from a Retrospective Pregnancy Cohort in a Rural Region of the Midwest - Julia Riddle; Julie A. Botsford; Samantha Dean; Carol Coffman; Chelsea A. Robinson; Jean M. Kerver (Mary Ann Liebert, 2023)
Background: Increasing numbers of pregnant women are being treated with buprenorphine for opioid use disorder (OUD), which can interfere with effectiveness of other opioids used for pain relief, making perioperative guidance for patients requiring cesarean delivery unclear. Methods: Using a retrospective cohort design, we abstracted 8 years of medical records (2013?2020) from a hospital in rural Michigan. We compared analgesic use (as a proxy for pain) and hospital length of stay (LOS) between groups of women with OUD whose buprenorphine treatment was (1) discontinued before cesarean delivery (discontinuation) versus (2) continued throughout the perioperative period (maintenance). We used t-tests and Fisher's Exact tests for comparison of continuous and categorical variables, respectively. Results: Maternal characteristics reflected the local population (87% non-Hispanic White; 9% American Indian). Of 12,179 mothers giving birth during the study timeframe, 87 met all inclusion criteria (2.4% with diagnosed OUD; 38% of those delivered by cesarean; 76% of those received prenatal buprenorphine treatment). Using the first 2 days of the hospital stay as the standard time window for comparison, there were no differences in perioperative opioid analgesic use (mean???standard deviation [SD]?=?141.6???205.4 vs. 134.0???136.3 morphine milligram equivalents, p?=?0.89) or LOS (mean???SD?=?2.9???0.9 vs. 3.3???1.0 days, p?=?0.14) between discontinuation (n?=?17) versus maintenance (n?=?70). There was a lower use of acetaminophen in the discontinuation group (mean???SD?=?3,842.6???2,108.1 vs. 4,938.2???2,008.4?mg, p?=?0.0489). Conclusion: This study provides empirical evidence supporting continued buprenorphine treatment for women with OUD throughout the perioperative period of a cesarean delivery in a rural setting, although replication with larger sample sizes would provide more confidence in the results.